Effect of Media Trainer on Electromagnetic Control and Industrial Panel on Learning Outcomes - Rachmawan, Adi Ika; Muslim, Supari; Suprianto, Bambang (Universitas Malikussaleh, 2019)
The purpose of this research is: (1) to determine the quality of the learning medium of electromagnetic control trainers and learning devices, and learning instruments using problem-based learning models; (2) to know the influence of students ' learning outcomes between the learning media of electromagnetic control trainers and industry panels on student learning outcomes. This type of research used was experimental quasi research with a quantitative approach and a Nonequivalent control group design. The learning outcomes in this study were the results of the study of the cognitive sphere, the study of the affective realm, and the results of learning psychomotor realm. Data collection is with test sheets on pretes and postes for cognitive learning outcomes, observation sheets of students learning attitudes for the results of the affective realm and observation sheets for psychomotor realm learning outcomes. The results showed that: (1) The learning medium of electromagnetic control trainers, learning devices, and learning instruments using problem-based learning models received excellent quality results; (2) Learning results of students who learn to use the learning media of the higher electromagnetic control trainer significantly compared to the learning outcomes of students who learn using industrial panel media.